Clinical features and 123I-FP-CIT SPECT imaging in vascular parkinsonism and Parkinson's disease. Issue 2 (20th August 2012) - Benítez-Rivero, Sonia; Marín-Oyaga, Víctor A; García-Solís, David; Huertas-Fernández, Ismael; García-Gómez, Francisco J; Jesús, Silvia; Cáceres, María Teresa; Carrillo, Fátima; Ortiz, Ana M; Carballo, Manuel; Mir, Pablo
Abstract : Objectives: To analyse the differences in the clinical features and characteristics of 123 I-labelled 2β-carbomethoxy-3β-(4-iodophenyl)-N-(3-fluoropropyl) nortropane ( 123 I-FP-CIT) single photon emission CT (SPECT) imaging among patients with vascular parkinsonism (VP) and Parkinson's disease (PD). Methods: We performed a case–control study to compare clinical features and qualitative and semi-quantitative analyses of 123 I-FP-CIT SPECT images between 106 patients with VP and 280 patients with PD. A case series study was used to search for clinical features related to SPECT or neuroimaging findings among patients with VP. Results: Patients with VP had a higher age at symptom onset and lower disease duration than patients with PD. The most frequent symptom at onset was gait disorder in VP and tremor in PD. Gait disorder, postural instability and falls were more frequent in VP. Rest and mixed tremor were more prevalent in PD. Of the patients who received levodopa treatment in the VP group, only about half had a good response. Qualitatively 123 I-FP-CIT SPECT images were normal in 32.5% of patients with VP and abnormal in all patients with PD. The use of different visual score patterns showed higher ability to differentiate VP from PD. Semi-quantitative analysis showed significantly higher uptake in the striatum, caudate and putamen in VP. The asymmetry index was higher in patients with PD. Among patients with VP, falls were the only clinical feature that demonstrated a correlation with the SPECT visual pattern. Conclusion: Our data contribute to the confirmation that VP and PD are two different clinical entities. Neurological signs, response to treatment and qualitative and semi-quantitative 123 I-FP-CIT SPECT analyses may help to make the diagnosis.